"I'm going to be forced to have a baby": A study of COVID‐19 abortion experiences on Reddit. - Jacques, Laura; Valley, Taryn; Zhao, Shimin; Lands, Madison; Rivera, Natalie; Higgins, Jenny A. (Perspectives on Sexual & Reproductive Health, 2023)
Introduction: The initial stages of the COVID‐19 pandemic affected abortion care in the United States (US) in myriad ways. While research has documented systems‐level pandemic‐related impacts on abortion access and care delivery little information exists about the experiences of abortion seekers during this period. We sought to document the effects of COVID‐19 pandemic restrictions US abortion seekers by analyzing posts on Reddit, a popular social media website. Methods: We compiled and coded 528 anonymous posts on the abortion subreddit from 3/20/2020 to 4/12/2020 and applied inductive qualitative analytic techniques to identify themes. Results: We identified four primary themes. First, posters reported several COVID‐19‐related barriers to abortion services: reduced in‐person access due to clinic closures, mail delivery delays of abortion medications, and pandemic‐related financial barriers to both self‐managed and in‐clinic abortion. The second theme encompassed quarantine‐driven privacy challenges, primarily challenges with concealing an abortion from household members. Third, posters detailed how the pandemic constrained their pregnancy decision making, including time pressure from impending clinic closures. Finally, posters reported COVID‐19‐related changes to service delivery that negatively affected their abortion experiences, for example being unable to bring a support person into the clinic due to pandemic visitor restrictions. Discussion: This analysis of real‐time social media posts reveals multiple ways that the COVID‐19 pandemic limited abortion access in the US and affected abortion seekers' decisions and experiences. Findings shed light on the consequences of sudden changes, whether pandemic or policy related, on abortion service delivery.